A behavioral economic analysis of texting while driving: Delay discounting processes. (December 2016) - Hayashi, Yusuke; Miller, Kimberly; Foreman, Anne M.; Wirth, Oliver
Highlights: We examined an impulsive decision-making process underlying texting while driving. Students who frequently text while driving discounted delayed opportunities to reply to a text message at a greater rate than students who do not frequently text while driving. The rates of discounting delayed opportunities to reply were best described by a hyperbolic delay discounting function. There was no relation between the frequency of texting while driving and the discounting rate of another delayed reward—hypothetical money. Texting while driving is fundamentally an impulsive choice made by drivers. Abstract: The purpose of the present study was to examine an impulsive decision-making process underlying texting while driving from a behavioral economic perspective. A sample of 108 college students completed a novel discounting task that presented participants with a hypothetical scenario in which, after receiving a text message while driving, they rated the likelihood of replying to a text message immediately versus waiting to reply for a specific period of time. Participants also completed a delay discounting task in which they made repeated hypothetical choices between obtaining a larger amount of money available after a delay and an equal or lesser amount of money available immediately. The results show that the duration of the delay is a critical variable that strongly determines whether participants choose to wait to reply to a text message, and that the decrease in the likelihood of waiting as a function of delay is best described by a hyperbolic delay discounting function. The results also show that participants who self-reported higher frequency of texting while driving discounted the opportunity to reply to a text message at greater rates, whereas there was no relation between the rates of discounting of hypothetical monetary rewards and the frequency of texting while driving. The results support the conclusion that texting while driving is fundamentally an impulsive choice.